2021
DOI: 10.1111/tpj.15185
|View full text |Cite
|
Sign up to set email alerts
|

Cell wall‐derived mixed‐linked β‐1,3/1,4‐glucans trigger immune responses and disease resistance in plants

Abstract: Pattern-triggered immunity (PTI) is activated in plants upon recognition by pattern recognition receptors (PRRs) of damage-and microbe-associated molecular patterns (DAMPs and MAMPs) derived from plants or microorganisms, respectively. To understand better the plant mechanisms involved in the perception of carbohydrate-based structures recognized as DAMPs/MAMPs, we have studied the ability of mixed-linked b-1,3/1,4-glucans (MLGs), present in some plant and microbial cell walls, to trigger immune responses and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
137
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 98 publications
(162 citation statements)
references
References 77 publications
(163 reference statements)
16
137
1
8
Order By: Relevance
“…Whether or not this also holds true for glucose trimers and cellodextrins, which have recently been shown to have comparatively higher elicitor activities ( Locci et al, 2019 ) remains to be shown. However, our data are in conflict with the observations of Rebaque et al (2021) , who suggest that MLG perception is at least partially dependent on CERK1, LYK4, and LYK5. It is hard to rationalize this discrepancy, but the direct comparison of β-1,3/1,4-MLG oligosaccharide-induced MAPK activation in the wildtype and corresponding mutant genotypes that we conducted on the same membrane revealed no significant difference.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Whether or not this also holds true for glucose trimers and cellodextrins, which have recently been shown to have comparatively higher elicitor activities ( Locci et al, 2019 ) remains to be shown. However, our data are in conflict with the observations of Rebaque et al (2021) , who suggest that MLG perception is at least partially dependent on CERK1, LYK4, and LYK5. It is hard to rationalize this discrepancy, but the direct comparison of β-1,3/1,4-MLG oligosaccharide-induced MAPK activation in the wildtype and corresponding mutant genotypes that we conducted on the same membrane revealed no significant difference.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to monocot species, dicot plants such as A. thaliana do not contain β-1,3/1,4-MLGs in their cell walls (Zablackis et al, 1995;Burton and Fincher, 2009). However, the experimental data of this work and a recently published study (Rebaque et al, 2021) clearly demonstrate that Arabidopsis plants can detect β-1,3/1,4-MLG oligosaccharides and react with canonical PTI responses. As β-1,3/1,4-MLG oligosaccharides are not present in Arabidopsis, they are likely to function as a MAMP in this species.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations